Challenges of Management in the COVID-19 Reality: Journal of East European Management Studies (JEEMS) – Special Issue - Wieczorek-Kosmala, Monika; Gurkov, Igor; Steger, Thomas (Nomos Verlagsgesellschaft mbH & Co. KG, 2022)
The emergence of the COVID-19 pandemic, with its multidimensional impacts on organisational management, inspired this special issue. The issue presents a collection of full-length articles and research reports devoted to the experiences of enterprises during the first year of the pandemic in various East European countries (Poland, Hungary, the Czech Republic, Russia, Armenia, and Bosnia and Herzegovina). The contributions range from in-depth studies on a pair of similar subsidiaries of multinational companies or on small and medium size enterprises, to the attempts to present trends and tendencies in particular sectors or to study the impact of the COVID-19 pandemic on the management of different types of enterprises in the national economy.With contributions byMane Beglaryan, Almina Bešić, Robin Čejka, Mariola Ciszewska-Mlinarič, Gergely Freész, Vache Gabrielyan, Tim Gittins, Igor Gurkov, Christian Hirt, Loretta Huszák, Bogna Kaźmierska-Jóźwiak, Sergey Lapshin, Tadeusz Milancej, Krzysztof Obłój, Zijada Rahimić, Tomáš Sadílek, Paweł Sekuła, Gayane Shakhmuradyan, Ivan Shchetinin, Błażej Socha, Thomas Steger, Aleksandra Wąsowska, Monika Wieczorek-Kosmala and Piotr Wójcik.